The mechanism of the inhibitory effect of progesterone on lymphocyte cytotoxicity II. Relationship between cytotoxicity and the cyclooxygenase pathway of arachidonic acid metabolism - Szekeres-Bartho, J (American journal of reproductive immunology and microbiology : AJRIM, 1985)
In the previous paper we have demonstrated that progesterone-treated lymphocytes of healthy pregnant women produce a 34,000 MW protein that inhibits cytotoxic activity and prostaglandin F2 alpha synthesis. Since recently it has been shown that certain leukotrienes have a stimulatory effect on natural killer activity, in this study an attempt was made to determine whether there is a relationship between cytotoxicity and PGF2 alpha synthesis or if alterations in the values of these parameters are independent. Arachidonic acid increased cytotoxic activity of healthy pregnant women's peripheral blood mononuclear cells (PBMC) in a concentration-dependent manner. Exogenous arachidonic acid was able to counteract the blocking effect of the above-mentioned protein produced by progesterone-treated lymphocytes. To determine whether the products of the cyclooxygenase or the lipoxygenase pathway of arachidonic acid metabolism are responsible for increased cytotoxicity, both enzyme systems were blocked separately. Both indomethacin and the lipoxygenase inhibitor BW 755C reduced cytotoxicity in a dose-dependent fashion. However, the lipoxygenase inhibitor prevented prostaglandin synthesis to the same extent, or even more than indomethacin, in all concentrations used; so, its blocking effect cannot be considered as supportive evidence for the role of leukotrienes in cytotoxicity. On the other hand, lipopolysaccharide, with a selective stimulatory effect on prostaglandin synthesis, increased cytotoxicity. Lipopolysaccharide had no effect on progesterone-pretreated PBMC. The above data allow the assumption that besides leukotrienes, cyclooxygenase products may also increase cytotoxicity